(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we discuss the existence of positive periodic solutions for nonlinear functional difference equations. We illustrate the applicability of our main result by examining the Lasota–Wazewska, the Mackey–Glass and the Nicholson’s Blowflies models.